Efecto de la aplicación de fitohormonas sobre el crecimiento y desarrollo del cultivo de maracuyá (Passiflora edulis f. flavicarpa) INIAP 2009 - Franco Reyes, Milton Gabriel (2023)
Passion fruit (Passiflora edulis f. flavicarpa) is a crop that presents an increasing demand at the national level. The use of growth regulators as a strategy to improve passion fruit production is an almost unknown practice in the Zapotillo canton; for this reason, it was proposed to evaluate the effect of the application of the hormones Gibberellin and Cytokinin, in the growth and development of the plant and the fruit, considering doses of 20 and 40 ppm. For this purpose, an experiment was carried out in the Garza Real of the experimental farm South Cost from Instituto Nacional de Investigaciones Agropecuarias -INIAP, through the implementation of a design (DCA) with factorial arrangement of 7 phytohormone treatments 5 repetitions plus a control. The goal of this study was to evaluate the effect of the application of two phytohormones (gibberellin and cytokinin). Within the measurements, the following variables were recorded: number of guides per plant, internode distance, number of flowers per plant, number of fertilized fruits, fruit weight (gr), total soluble solids (TSS), titratable acidity (%), pH. As part of the results, until the end of the research treatment 7 (Gibberellins and cytokinins 40 ppm) in the number of guides and the distance between nodes presented averages between 43.20 and 8.54 respectively, which indicates that the applications were effective. Cytokinins at 20 ppm increased the number of flowers, while, simultaneously applying Gibberellins and cytokinins at 20 ppm this variable gradually declined; On the other hand, the treatment 7 (x + y) with the highest yield for the variable fruit weight was the combination (gibberellin 20 ppm – cytokinin 20 ppm). In general, when evaluating the organoleptic characteristics of the fruit, there not statistically significant differences were evident. Keywords: Cytokinins, Gibberellins.